An analysis of the practices of caesarean section in sub-Saharan Africa: A summary of the literature - Dikete, Michel; Coppieters, Yves; Trigaux, Philippe; Englert, Yvon; Simon, Philippe; Zhang, W (Archives of Community Medicine and Public Health, 2019)
Introduction: Ensuring access to quality caesarean sections (CS) is a challenge for the next millennium and a sustainable development goal to reduce maternal and infant mortality. A CS involves risks and complications and should therefore be performed in an approved way and not used excessively. The WHO recommends that the CS rate should not exceed 10–15%. Approximately 99% of maternal deaths occur in developing countries where efforts to reduce maternal deaths are still low. This review of the literature aims to provide a summary of CS practices in sub-Saharan Africa and the consequences in terms of morbidity and mortality. Material and Method: The data was collected following the selection criteria on the NCBI’s PubMed. Result: Across the four main themes selected for this summary, the frequency of CS varies from 2 to 51%. Indications for caesarean CS are mainly dystocia, foetal distress, scarred uterus, breech presentation, antenatal haemorrhage and hypertensive disorders. Maternal risks related to CS are surgical site infections, obstetric fistulae, anaesthetic complications, pulmonary embolism, postpartum haemorrhage, haemostatic hysterectomy and maternal death, and the perinatal risks related to CS are respiratory distress, prematurity and perinatal death. Conclusion: In the current working conditions, the risks incurred by the mother and the foetus during a CS are significantly greater than during a vaginal delivery. CS is not yet a factor in reducing maternal and perinatal morbidity and mortality in Sub-Saharan Africa. To reduce maternal and perinatal morbidity and mortality, working conditions at referral centre level, transfer conditions, and improve the training of health staff should be improved.